2020
DOI: 10.1111/odi.13606
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on dental activity during COVID‐19: The Italian survey

Abstract: Objectives During the months of March and April 2020, Italy saw an exponential outbreak of COVID‐19 epidemic. Dental practitioners were particularly limited in their routine activity, and the sole performance of urgent treatments was strongly encouraged during the peak of the epidemic. A survey among dental professionals was performed between 6 th ‐13 th of April, in order to evaluate the status of dental practice during COVID‐19 in Italy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 26 publications
7
55
3
4
Order By: Relevance
“…We sought to discover if there were merely a correlation or a substantial causative effect between unemployment among dental specialty workers and future COVID-19 vaccine acceptance. Dentistry is unique in that it is a private-sector workforce which, unlike most healthcare fields, was forced to discontinue non-essential operations in Israel, as well as in other countries, during the pandemic ( 17 ). This characteristic can allow extrapolations from questionnaires distributed to dentistry or dentistry-auxiliary employees regarding unemployment and vaccine willingness.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to discover if there were merely a correlation or a substantial causative effect between unemployment among dental specialty workers and future COVID-19 vaccine acceptance. Dentistry is unique in that it is a private-sector workforce which, unlike most healthcare fields, was forced to discontinue non-essential operations in Israel, as well as in other countries, during the pandemic ( 17 ). This characteristic can allow extrapolations from questionnaires distributed to dentistry or dentistry-auxiliary employees regarding unemployment and vaccine willingness.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in patients recorded during lockdown and the second wave in the UDCS could be a consequence of either a raising awareness about what should be considered a dental emergency and a widespread fear of going to an emergency department and/or hospital [27]. Dental activities have since struggled to recover because of ongoing economical and healthcare difficulties such as shortages of personal protective equipment and delayed admissions in dental offices due to the COVID-19 restrictions [14,28]. The peak registered during the reopening might be the consequence of a partial incapacity of the private dental healthcare system to meet patient needs during the first pandemic recovery.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the emergency guidance, the Association has added urgent dental care, which focuses on the management of conditions that require immediate attention to relieve severe pain and/or risk of infection [13]. A survey performed among Italian dentists during the first wave of COVID-19 showed that the most common urgent procedures provided were the treatment of pulpitis, dental abscess, and prosthesis re-cementation [14].…”
Section: Introductionmentioning
confidence: 99%
“…12 Several protocols have been suggested for protection of eyes, nasal and oral mucosa during COVID-19 outbreak. 13 In the current study, more than 95% of the respondents agreed to the fact that dentists and dental chair side assistants should get proper training regarding donning and doffing of PPEs. In a study done by Stefani et al 14 57.2% of respondents declared that they were not trained sufficiently regarding donning and doffing of PPEs and gave a consensus that training of staff should be the top priority.…”
Section: Discussionmentioning
confidence: 63%
“…This is in accordance with the study carried out in Italy, where 99.7% of respondents preferred to perform only urgent treatments. 13 According to a survey carried out earlier, dental care for patients is limited to emergency treatment in most developed countries. 23 According to British endodontic society, advise for clinicians for management of dental emergencies is Advice, Analgesia and Antibiotic (where required) approach.…”
Section: Discussionmentioning
confidence: 99%